2023
DOI: 10.1101/2023.02.16.528839
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Transcriptional heterogeneity in human diabetic foot wounds

Abstract: Wound repair requires the coordination of multiple cell types including immune cells and tissue resident cells to coordinate healing and return of tissue function. Diabetic foot ulceration is a type of chronic wound that impacts over 4 million patients in the US and over 7 million worldwide (Edmonds et al., 2021). Yet, the cellular and molecular mechanisms that go awry in these wounds are not fully understood. Here, by profiling chronic foot ulcers from non-diabetic (NDFUs) and diabetic (DFUs) patients using s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 56 publications
1
4
0
Order By: Relevance
“…We found upregulated IGHG1, IGHG2, IGHG3, GLV3-21, IGLV6-57, CD177, HIST1H2AJ, HIST1H2AL, HIST1H2BM, HIST1H3B, and HIST1H3G genes from PBMC during active phase of S. aureus infection in patients with DFU at 0 weeks; these genes became downregulated at 8 weeks among healed patients, and these transcriptomes may reflect infectivity before and after antibiotic therapy. In line with the report by Sandoval-Schaefer et al (2023) on transcriptional heterogeneity in human diabetic foot wounds, it was reported that profiling chronic foot ulcers from non-diabetic and diabetics patients using single-cell RNA sequencing display transcription changes in gene expression that may provide therapeutic baseline for treatment of DFU. Our findings further add evidence to the existing knowledge that transcriptome profiling of RNA-seq can delineate genes signatures and could be a potential valuable technique for diagnosing infection, determining severity, and measuring host immune response to therapies.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…We found upregulated IGHG1, IGHG2, IGHG3, GLV3-21, IGLV6-57, CD177, HIST1H2AJ, HIST1H2AL, HIST1H2BM, HIST1H3B, and HIST1H3G genes from PBMC during active phase of S. aureus infection in patients with DFU at 0 weeks; these genes became downregulated at 8 weeks among healed patients, and these transcriptomes may reflect infectivity before and after antibiotic therapy. In line with the report by Sandoval-Schaefer et al (2023) on transcriptional heterogeneity in human diabetic foot wounds, it was reported that profiling chronic foot ulcers from non-diabetic and diabetics patients using single-cell RNA sequencing display transcription changes in gene expression that may provide therapeutic baseline for treatment of DFU. Our findings further add evidence to the existing knowledge that transcriptome profiling of RNA-seq can delineate genes signatures and could be a potential valuable technique for diagnosing infection, determining severity, and measuring host immune response to therapies.…”
Section: Discussionsupporting
confidence: 55%
“…The shift from the use of convectional culture-dependent methodologies and serum antibody levels to transcriptome analysis may help us better understand DFU infection, patient outcomes, and wound progression. Few research studies have recently elucidated the role of RNA-seq/transcriptomes in DFU ( Theocharidis et al., 2020 ; Wang et al., 2020 ; Li Y, et al., 2022 ; Theocharidis et al., 2022 ; Sandoval-Schaefer et al., 2023 ). Transcriptome data analysis, for example, has been utilized to identify gene expression profiles, biological signal pathways, and biomarkers in various diseases such as cancer, tuberculosis, neuronal dysfunction, autoimmune diseases, and COVID-19 prognosis ( Baine et al., 2011 ; Islam et al., 2017 ; Bellaver et al., 2019 ; Wang et al., 2019 ; Xiong et al., 2020 ; Zheng et al., 2020 ; Fang et al., 2021 ; Han et al., 2021 ; Ascoli et al., 2022 ; Ghosh et al., 2022 ; Maleknia et al., 2022 ; Mendelsohn et al., 2022 ; Zimmer et al., 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…The process of converting gene information into products that cells can recognise is called gene expression (Sandoval-Schaefer et al, 2023). The result of this gene expression can be a protein and an RNA product such as tRNA or snRNA (Ramirez-Acuña et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…This study used single-cell RNA sequencing technology on cells taken from the foot wounds of a non-diabetic individual at different times and from five diabetic patients. The cells were isolated through mechanical and enzymatic breakdown, screening, and removal of red blood cells, then retrieved via single-cell RNA sequencing technology using the 10X Genomics platform (Sandoval-Schaefer et al, 2023).…”
Section: Gse223964 Gene Codementioning
confidence: 99%
“…Mathematical modeling of lymphangiogenesis in diabetic human wounds suggests potential applications for treating such conditions ( Bianchi et al, 2015 ). Additionally, single-cell transcriptomic analyses of human diabetic foot wounds have revealed significant alterations in various signaling pathways, including those related to lymphatic vessels ( Sandoval-Schaefer et al, 2023 ), underscoring the importance of exploring the mechanisms regulating lymphangiogenesis for the treatment of diabetic wounds. In mouse models, a clear link has been established between impaired diabetic wound healing and hindered lymphatic vessel formation due to reduced macrophage activity ( Maruyama et al, 2007 ).…”
Section: Lymphatic Vessels In Skin Wound Healing: New Avenues To Expl...mentioning
confidence: 99%